Labour Absorption in Livestock Activities in Arid Western and Northern Region of Rajasthan - Mishra, Siddhartha (Indian Journal of Dairy Science, 2022)
In the arid western and northern regions of Rajasthan livestock activity is a complementary activity to farming and it provides much needed risk cover in case of crop failure. The present investigation was undertaken to study the labour absorption in different livestock activities in Arid western and northern regions of Rajasthan. The study was conducted based on primary data. The primary data were collected from the 200 households of 10 villages during year of the 2018-2019. The average utilization of human labour in livestock activities was found 54.48 man-days/animal/year in arid western and northern region. The participation of woman labour in all livestock activities was found more than man labour in all herd size group in arid western and northern region. The annual average human labour absorption was maximum in site preparation activity i.e., 28.76 hours/animal/year for male and 101.63 hours/animal/year for female, then other activities in all size of farms